Corporate Compliance with Acquisition Notification Obligations to the KPPU: A Legal Review of Article 29 of Law No. 5 of 1999 (Case Study of TikTok Nusantara – Tokopedia) - Aslamiyah, Mujadiddah; Falah, Nabilah; Gunawan, M Safaat; Paqih, Ibnu (Universitas Negeri Semarang, 2025)
The notification of a company acquisition based on Article 29 of Law No. 5 of 1999 concerning Prohibition of Monopoly and Unfair Business Competition is an obligation that must be fulfilled by business actors. In January 2024, TikTok Nusantara (SG) Pte. Ltd acquired shares in the company PT Tokopedia, Tbk, which resulted in an obligation to report or notify the Business Competition Supervisory Commission (KPPU) of the purchased shares. However, based on KPPU Decision Number 02/KPPU-M/2025, there was a delay in notification from TikTok Nusantara (SG) Pte. Ltd as the acquiring party to the KPPU. The cross-border transaction involving the Big Tech entity resulted in administrative sanctions in the decision. However, in its defense as mentioned in the decision, the acquiring party stated that it had submitted a post-acquisition notification, but the reporting party was its parent company, TikTok Pte. Ltd, so the KPPU considered that there was a violation related to the legal entity obliged to submit the notification, particularly in the context of using a foreign Special Purpose Vehicle (SPV) as the acquiring entity. The main issue lies in the ambiguity of the identity of the party considered to be the acquiring party’s legal entity, and the effective time of the transaction used as the basis for calculating the notification deadline. This study uses a normative juridical method with a case approach to KPPU Decision Number 02/KPPU-M/2025. The unclear legal status of SPVs in multinational corporate structures has the potential to create legal uncertainty and hamper the effectiveness of market concentration supervision in the digital sector.